RESEARCH CONCERNING THE DYNAMIC ANALYSIS OF A CRANK AND CONNECTING ROD MECHANISM - Georgeta Toma; Dorin Badoiu (Romanian Journal of Petroleum & Gas Technology, 2020)
The paper analyzes the influence of some parameters regarding the configuration and the operation of the crank and connecting rod mechanism on the variation of the motor torque and on the values of the connecting forces in the joints.